(untitled) (Research, Society and Development, 2021)
The demand for soybean has increased in the international market, and water restriction is an important factor in reducing its yield. Therefore, the development of technologies aimed to reducing the damage caused by water stress becomes strategic. Thus, the objective was to demonstrate the role of the amino acid L-glutamic acid in mitigating water stress in soybean plants. A study was conducted in a greenhouse using soybean plants in vegetative stage subjected to water restriction and foliar applications of biofertilizer obtained from bacterial fermentation, containing 25% of the amino acid L-glutamic acid, sprayed three days before the imposition of water restriction and when the substrate moisture reached 50% of the water retention capacity (WRC). Stomatal resistance was determined throughout the days and three collections of plant material were carried out: at the beginning of water restriction, one and four days after rehydration for biochemical and enzymatic analyses. Plants that were supplied with biofertilizer at the beginning of water restriction showed lower stomatal resistance, while plants that received application three days before 50% WRC showed increases in sugar accumulation, in free amino acids and proline content, and in nitrate reductase and peroxidase enzymes activity, consequently, reducing lipids peroxidation, mitigating the effects of oxidative stress.